Policies and Planning for Low-Carbon Power Systems - Olsen, Daniel Julius Burle (My University, 2019)
Mitigating the worst effects of anthropogenic climate change is a pressing global concern which will require steep cuts in emissions of greenhouse gases, including from power systems. In line with over a century of research into environmental economics, private industry has little incentive to provide enough emissions reductions unless induced to do so by effective public policy. There has been considerable research into energy and environmental economic policies, as well as into the technical potential for power systems to be planned and operated for lower carbon emissions, but so far the literature lacks an intersection of these two areas. This dissertation is intended to fill that gap, by presenting detailed technical models of power systems embedded within policy design problems for lowering carbon emissions. Four policy design models are proposed in detail: i) Electrification of transportation will likely lead to large increases in at-home vehicle charging, which can stress residential distributions systems that were not planned for this level of peak evening demand. The deployment of home energy management systems will tend to shift loads towards traditional off-peak hours, but may end up creating new local peaks. How can distribution system operators manage the transition of their customers to more electrified transportation and price-responsive load scheduling? ii) Power systems present one of the most practical opportunities for quick emissions reductions, as fuel-switching on the back-end can significantly reduce emissions with no change in the quality or quantity of power delivered to consumers. However, many power systems are operated at minimum fuel cost and allow carbon dioxide to be emitted for free, or have a price on emissions that is ineffective in driving deep decarbonization. How can we design a carbon tax rate that achieves a given emissions reduction target at minimum cost increase? iii) Much of the world's primary energy consumption is ultimately induced by the consumption of secondary energy within buildings. If we are designing new campus-scale energy infrastructure, which energy conversion and storage equipment should we install to meet our target target for induced emissions? If we only have control of equipment choices via building codes, what are the relative efficiencies of these less direct policy measures? iv) Grid-scale energy storage is often touted as the answer to the problem of the intermittency of renewable generation. However, if installed in current power systems and operated without regard for marginal emissions rates, it is likely to increase carbon emissions. If we mandate an `emissions neutrality constraint'--the impact of storage operation on power systems cannot be to increase emissions--how does this change power system emissions, operating costs, and investment in grid-scale energy storage? The use of these policy design approaches in broader-scale decarbonization models is discussed, and several more projects in the same vein are proposed for future work.
Thesis (Ph.D.)--University of Washington, 2019
Keywords: Climate policy; Multi-level models; Optimization; Power systems; Electrical engineering; Environmental economics; Public policy; Electrical engineering